A case–control study to find the association between iron deficiency anemia and simple febrile seizures in children between 6 months and 5 years of age group - Vaghela, Radhika; Mandot, Sanjay (Indian Journal of Child Health, 2020)
Background: Simple febrile seizure (FS) is the most common type of childhood seizure. Iron plays an important role in brain metabolism, neurotransmitter function, and myelination. Iron deficiency anemia (IDA) has been found to be associated with an increased incidence of FS. Objective: The objective of the study was to study the prevalence of IDA in simple FS patients and febrile patients without seizure. Materials and Methods: All admitted febrile children between 6 months and 5 years were enrolled in the study according to the inclusion and exclusion criteria and a detailed clinical examination was done. Blood samples were collected for complete blood count, blood indices, and serum ferritin. Results: IDA was present in 28 out of 50 patients in the case group and 18 of 50 patients in the control group (p